The Critical Cycle of Mixtape Creation: Reducing Stress via Three Different Group Counseling Styles. Issue 4 (1st October 2020) - Levy, Ian; Travis, Raphael
ABSTRACT: While significant attention has been given to student learning loss across summer, much less attention is given to student stressors and mental health concerns. To assist youth in processing and coping with emotional stress, research explores approaches to group counseling wherein youth write, record, and perform emotionally themed hip hop mixtapes. Hip hop, counseling, and social work literature lack studies comparing the effectiveness of different group types. This study examined a hip hop integrated therapeutic model within three groups using distinct leadership styles; within a high school summer enrichment program. Results suggest statistically significant reductions in stress and depressive levels.